The Implementation of Online Assessment at Junior High Schools in Tasikmalaya - Risma Maudhira Khoeriyah; Lystiana Nurhayat Hakim; Sundari Purwaningsih (Journal of Applied Linguistics (ALTICS), 2021)
This research that aims to investigating how teachers implement of online assessment at junior high schools and find out the challenges faced by the teachers in implementation of online assessments in English lesson at junior high schools in Tasikmalaya. This study takes place at junior high schools in Tasikmalaya. This study sample 6 English teachers were chosen purposive sampling technique. This research is classifying as case study. Case study is using because this approach can develop more in-depth analysis of a case (Cresswell, 2018, p.295). This research is a suitable a case study because it raises a phenomenon that is currently happening in Tasikmalaya. In the results of this study found online assessment tools used by teachers, namely Google Classroom, Google Form, WhatsApp, Zoom, and which are less frequently used, namely Blogs and Quizizz. Based on the data generated from the interview there are obstacles encountered by teachers like often finding students asking for delays in assessment, late students in work collections, trouble seeing student insights, trouble getting feedback because it's hard to contact a few students. Keywords: Online Assessmennt, Four Language Skills, Online Assessment Tools, Challenges and Strategies